Research on the multi energy complementation of wind power consumption (International Journal of Engineering and Computer Science, 2018)
Multi energy complementation has gradually become a research hotspot in the future power system. For the whole multi energy complementary system, its fundamental purpose is to consider the stability of the overall power output. In this paper, the composition of multi energy complementary energy and the form of multi energy complementary function are analyzed, and the minimum mathematical model of the whole power fluctuation is established. The particle swarm optimization (PSO) is used to carry out a simulation study in a certain area of Xinjiang. It is concluded that the multi energy complementation is an effective means to improve the quality of wind power distribution and to solve the problem of abandoning the wind. Through the combination of clean energy forms such as solar energy and hydropower, the use value of new energy is fully developed, and the use of traditional fossil energy is reduced, and the wind power consumption has a positive effect.